Network-Like Platinum Nanosheets Enabled by a Calorific-Effect-Induced-Fusion Strategy for Enhanced Catalytic Hydrogenation Performance - Chen, Ting-Wen; Pang, Da-Wei; Kang, Jian-Xin; Zhang, Dong-Feng; Guo, Lin (Frontiers in Chemistry, 2022)
In this paper, we report the construction of network-like Pt nanosheets based on Pt/rGO hybrids by delicately utilizing a calorific-effect-induced-fusion strategy. The tiny Pt species first catalyzed the H2-O2 combination reaction. The released heat triggered the combustion of the rGO substrate under the assistant of the Pt species catalysis, which induced the fusion of the tiny Pt species into network-like nanosheet structure. The loading amount and dispersity of Pt on rGO are found be crucial for the successful construction of network-like Pt nanosheets. The as-prepared products present excellent catalytic hydrogenation activity and superior stability towards unsaturated bonds such as olefins and nitrobenzene. The styrene can be completely converted into phenylethane within 60 min. The TOF value of network-like Pt nanosheets is as high as 158.14 h-1, which is three times higher than that of the home-made Pt nanoparticles and among the highest value of the support-free bimetallic catalysts ever reported under similar conditions. Furthermore, the well dispersibility and excellent aggregation-resistance of the network-like structure endows the catalyst with excellent recyclability. The decline of conversion could be hardly identified after five times recycling experiments.